Seroprevalence of hepatitis B virus infection among children and adolescents in Singapore, 2008–2010. Issue 4 (8th February 2013) - Ang, Li Wei; Tey, Su Hui; Cutter, Jeffery; James, Lyn; Goh, Kee Tai
Abstract A national pediatric survey was undertaken to determine the prevalence of hepatitis B virus markers in Singapore. The aim was to assess the impact of the national childhood immunization program against hepatitis B implemented for all newborns since 1987. The survey involved prospective collection of residual sera from Singapore residents aged 1–17 years attending inpatient services or day surgery in two public hospitals between August 2008 and July 2010. A total of 1, 200 sera were collected comprising 400 in each of the three age groups of 1–6, 7–12, and 13–17 years. The sera were tested for hepatitis B surface antigen (HBsAg) and antibody to HBsAg (anti‐HBs). Four of the 1, 200 samples tested positive for HBsAg, giving an overall prevalence of 0.3%. One and three in the 7–12 years and 13–17 years age groups, respectively, were positive for HBsAg. About 40% possessed anti‐HBs (≥10 mIU/ml); the antibody prevalence decreased significantly from 63.8% in children aged 1–6 years to 32.8% in 7–12 year olds, and 23.5% in 13–17 year olds (P < 0.0005). The successful implementation of the national childhood hepatitis B immunization program over the last two decades has resulted in a low prevalence of HBsAg among children and adolescents. Singapore has achieved the World Health Organization Western Pacific Region's goal in reducing the prevalence of chronic HBV infection to below 2% among children aged 5 years and older by 2012 and to below 1% by 2017. J. Med. Virol. 85:583–588, 2013. © 2013 Wiley Periodicals, Inc.